Identifyling limitations, shortcomings, and solutions in the management of redundant public assets after the rearrangement of administrative units - Nguyen Quang Vinh (Journal of State Management, 2025)
The rearrangement of administrative units is a significant policy aimed at streamlining the apparatus, improving the effectiveness and efficiency of state management, and maximizing resource utilization for socio-economic development. However, after the rearrangement, a large volume of redundant public assets remains scattered across many localities, while the mechanisms for managing, utilizing, and allocating these resources have not been promptly adjusted to the new model. This situation poses risks of waste, inefficient use, or even abandonment and deterioration of assets. Based on an analysis of the current management of redundant public assets following the restructuring of administrative units, this article identifies key difficulties and inadequacies in mechanisms, policies, and implementation practices. It then proposes several solutions to prevent waste, enhance the efficient use of public assets, and unlock the potential value of state resources, thereby ensuring sustainability in public asset management.